2009
DOI: 10.1055/s-0029-1210255
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-Thyroid Function during Acute Immobilization Stress in Rats

Abstract: In nine experiments a total of 394 male Wistar rats weighing about 300 g was used. In each experiment, one intact control group was used and several other groups were subjected to immobilization (IMO) for 2 to 240 min in a prone position by inserting their heads through steel wire loops fixed on a board and by fasting their limbs to four metal strips by adhesive tape. All animals were killed by decapitation and the levels of thyrotropin (TSH), thyroxine (T4), 3,5,3'-triiodothyronine (T3) and 3,3',5'-triiodothy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…Aligned with these results, there are other studies that have reported long-time stress does not influence thyroid hormones (13). However, there are other studies that show thyroid hormone levels decrease during chronic immobilization stress (7,30). Other studies also argue that chronic immobilization stress decreases plasma levels of TSH and hypothalamic TRH mRNA levels in young rats (32,33).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Aligned with these results, there are other studies that have reported long-time stress does not influence thyroid hormones (13). However, there are other studies that show thyroid hormone levels decrease during chronic immobilization stress (7,30). Other studies also argue that chronic immobilization stress decreases plasma levels of TSH and hypothalamic TRH mRNA levels in young rats (32,33).…”
Section: Discussionsupporting
confidence: 71%
“…There are several studies showing that acute immobilization stress activate pituitary-thyroid system in rhesus monkeys (29). Other studies showed that acute immobilization stress increases the secretion of thyroid hormone (7,13,30) and there are also another study showing that acute immobilization stress does not change serum level of TSH (4). Most of physiological stresses initially influence neurons aminergic and subsequently peptidergic neurons in cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research suggests that in rodents, circulating peripheral TH concentrations decrease in response to severe, uncontrollable stressors such as restraint stress or inescapable foot- or tailshocks (Langer et al, 1983, Bianco et al, 1987, Servatius et al, 2000, Helmreich et al, 2005, Helmreich et al, 2006, Helmreich and Tylee, 2011). These changes are likely due to a reduced secretion of these hormones by the thyroid gland (Helmreich and Tylee, 2011), but low T3 levels may also be the result of decreased activity of D1 in liver and kidney (Bianco et al, 1987).…”
Section: Gestational States and Conditions That May Alter Or Intermentioning
confidence: 99%
“…Comparing endocrine systems across species, TH function as permissive hormones important for transitions and plasticity (Tata, 2006), including puberty (Mann and Plant, 2010), seasonal breeding (Ebling and Barrett, 2008), and metamorphosis in amphibians (Crespi and Denver, 2005). Moreover, the hypothalamic-pituitary-thyroid axis (HPT) is also a stress responsive system (Langer et al, 1983, Armario et al, 1984, Turakulov et al, 1994, Cizza et al, 1996, Kondo et al, 1997, Servatius et al, 2000, Helmreich et al, 2005, Helmreich et al, 2006, Kilburn-Watt et al, 2010). …”
mentioning
confidence: 99%